Total factor productivity, technology transfer and absorptive capacity in developing Asian countries - Chuah, Soo Cheng (2016)
Technological progress or total factor productivity (TFP) is the main factor in sustaining economic growth in the long run. As technological follower, technology transfer is the main source of technology progress in developing Asian countries. Effectiveness of technology transfer requires adequate human capabilities to absorb and adapt foreign technological knowledge. This study attempts to study the relative contribution of TFP growth to economic growth and technological absorption of human capital in the technology transfer process by looking into gender aspect at different levels of education. Solow neoclassical growth accounting method is applied to investigate the contribution of TFP growth to economic growth. The logistic technology diffusion model is used to determine the impact of human capital gender on TFP growth through dual dimensions – innovation and technology transfer for a sample of 12 developing Asian countries over the period of 1970 -2009 by using panel data pooled Ordinary Least Square (OLS), fixed/ random effects model. The growth accounting estimation supports the assimilation views that TFP growth has significantly contributed to the output growth of developing Asian countries. The empirical results indicated that the aggregate of female and male educations is significant in the technology transfer process. In terms of gender disaggregate educational levels, female and male tertiary education showed higher absorptive capacity in facilitating technology transfer. The results also showed that autonomous technology transfer has significant impact on TFP growth. This study shows the absorptive capacity of female and higher education in the technology transfer in enhancing the growth of productivity. As such, several policies may be implemented to enhance the effectiveness of technology transfer process by augmenting tertiary education, reducing the gender education disparity, enhancing the rate of female participation in labour force. Sustaining the economic growth which is based on productivity is important at accelerating the economic development of Asian developing countries.